From Earth to Eternity: Investigating Bitumen and Clay Use in Byzantine Church Construction at Ashdod-Yam - Lorenzon, Marta; Ruano Posada, Lucía; Gkouma, Myrsini; Bouzaglou, Liora; Ebeling, Philip; Fantalkin, Alexander (Archäologischer Anzeiger, 2025)
This paper presents the results of an archaeometric analysis aiming to characterize bitumen and plastic earthen materials (PEM) samples brought to light at the Ashdod-Yam Byzantine church (Israel). The site, active from the late 4th or early 5th century CE, shows evident signs of destruction by fire towards the end of the 6th century CE. This destruction was evident from the large number of shattered roof tiles embedded in a hard, earthen matrix, suspected to be composed of clay and bitumen. Selected samples from this destruction layer underwent examination through pXRF, WD-XRF, ESEM and thin-section petrographic analyses (TSPA). The goal was to determine the roofing material composition through cost-effective archaeometric techniques, investigate its microstructures, and discern the manufacturing technologies employed. While clay use in ceiling structures is well-documented in Byzantine-period regional structures, bitumen application as an intermediate layer between tiles and ceiling has not been previously recorded, thus offering a new insight into specific construction practices.